2021
DOI: 10.1287/isre.2021.1019
|View full text |Cite
|
Sign up to set email alerts
|

And the Winner Is …? The Desirable and Undesirable Effects of Platform Awards

Abstract: We study platform firms’ decision to recognize innovation by complementors ex post through awards. Despite being purely symbolic, awards might set incentives for complementors’ product strategies that can eventually lead to both desirable and undesirable outcomes for the platform firm. We depart from signaling theory and derive hypotheses on the effects of awards on complementors’ product strategies. To test them, we implement a quasi-experiment in the context of the Google Android mobile platform and the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 78 publications
2
36
2
Order By: Relevance
“…Additionally, we contribute to past research that has demonstrated that product entry can create discovery of an entire category (Foerderer et al, 2021). However, we study how imitation impacts product discovery of individual products, where the original is linked to an imitation with a citation or a reference.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, we contribute to past research that has demonstrated that product entry can create discovery of an entire category (Foerderer et al, 2021). However, we study how imitation impacts product discovery of individual products, where the original is linked to an imitation with a citation or a reference.…”
Section: Discussionmentioning
confidence: 98%
“…To help in discovery, new products typically appear at the top of search results and are curated into lists (Aguiar & Waldfogel, 2018). These marketplaces also list related products (e.g., “ Customers also purchased ” or “ Similar Products” ) that serve a similar or complementary purpose (Dzyabura & Hauser, 2019), and implement certifications or awards (Foerderer, Lueker, & Heinzl, 2021; Rietveld, Schilling, & Bellavitis, 2019). These systems are critical to helping customers identify available products.…”
Section: Theorymentioning
confidence: 99%
“…For instance, platform awards represent a cooperative governance mechanism. They have been found to increase the winners' likelihood of multihoming in the short term (Foerderer et al, 2021), which is associated with a decrease in CE with the original platform. Hence, despite the positive evaluations of winning an award and gaining additional customer attention, complementors decided to reduce their engagement in the short term and focus on other platforms instead.…”
Section: Discussionmentioning
confidence: 99%
“…Four out of five cases used in testing topic-dominant treatment effect satisfy the assumption and three out of five cases satisfy in testing topic dispersion. Propensity score matching is used to investigate further with the cases where the assumption is violated, as suggested in the literature [57], [58]. The DID result shows that:…”
Section: Difference-in-differences Estimation On Performancementioning
confidence: 99%